2013
DOI: 10.1246/cl.131050
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Reduction Synthesis Using CaCN2 as Calcium and Carbon Sources for CaAlSiN3:Eu2+ Phosphor and Their Luminescence Properties

Abstract: High-quality powders of mixed metal nitride phosphor, CaAlSiN 3 :Eu 2+ , were successfully synthesized using only inexpensive and air-stable materials, viz. CaCN 2 , CaCO 3 :Eu 3+ , AlN, and Si 3 N 4 , with no impurities such as AlN or carbon residue by a CRN method even under conditions of normal N 2 pressure (0.1 MPa) and a moderate temperature of 1600°C for 57 h. The resultant phosphors were well crystallized and gave an intense red emission band peaking at about 650 nm by optimizing the dopant amount of Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Oxygen contents of the CaAlSiN 3 :Eu 2+ phosphors prepared from the (Ca,Eu)AlSi and (Ca,Eu)AlSiH x powders were 4.21 and 3.07 wt% (see Table 3, samples a and b) that were extremely high compare with the value of the CaAlSiN 3 :Eu 2+ phosphor synthesized by the CRN method using CaCN 2 as one raw material for reducing CaCO 3 to Ca 3 N 2 , CaCN 2 + CaCO 3 ? 2/3Ca 3 N 2 + CO 2 + CO + 1/2N 2 [28]. However, it is noted that, for the CaAlSiN 3 :Eu 2+ phosphor (sample b), the oxygen content is relatively low and thus, the emission intensity is higher than that of the sample (a).…”
Section: Photoluminescence Propertiesmentioning
confidence: 92%
“…Oxygen contents of the CaAlSiN 3 :Eu 2+ phosphors prepared from the (Ca,Eu)AlSi and (Ca,Eu)AlSiH x powders were 4.21 and 3.07 wt% (see Table 3, samples a and b) that were extremely high compare with the value of the CaAlSiN 3 :Eu 2+ phosphor synthesized by the CRN method using CaCN 2 as one raw material for reducing CaCO 3 to Ca 3 N 2 , CaCN 2 + CaCO 3 ? 2/3Ca 3 N 2 + CO 2 + CO + 1/2N 2 [28]. However, it is noted that, for the CaAlSiN 3 :Eu 2+ phosphor (sample b), the oxygen content is relatively low and thus, the emission intensity is higher than that of the sample (a).…”
Section: Photoluminescence Propertiesmentioning
confidence: 92%
“…At present, there are few reports about the synthesis of CaAlSiN 3 :Eu 2? phosphors through carbothermal method except for the research by Kim et al [23] with hazardous CaCN 2 as calcium and carbon sources. Very recently, Li et al [24] reported the carbothermal synthesis of CaAlSiN 3 :Eu 2?…”
Section: Introductionmentioning
confidence: 99%
“…Carbothermal reduction and nitridation (CTRN) method, employing less-expensive oxides/carbonates and carbon reductant as raw materials, was widely reported as a candidate to meet these requirements. [14][15][16][17][18] 17 Our previous work also reported the synthesis of CaAlSiN 3 :Eu 2+ by carbothermal route, using CaH 2 , AlN, Si 3 N 4 , Eu 2 O 3 , and graphite powder as raw materials. 18 It is well-known that employment of less-expensive and airstable oxides raw materials is one of the fascinating superiorities raw materials is one of the fascinating superiorities CTRN method.…”
Section: Introductionmentioning
confidence: 99%
“…through carbothermal method using CaCO 3 , AlN, Si 3 N 4 , Eu 2 O 3 , and C powder (2014); Kim et al. reported the carbothermal preparation of CaAlSiN 3 :Eu 2+ phosphor using hazardous CaCN 2 as calcium and carbon sources; Our previous work also reported the synthesis of CaAlSiN 3 :Eu 2+ by carbothermal route, using CaH 2 , AlN, Si 3 N 4 , Eu 2 O 3 , and graphite powder as raw materials . It is well‐known that employment of less‐expensive and air‐stable oxides raw materials is one of the fascinating superiorities raw materials is one of the fascinating superiorities CTRN method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation